Motivational Strategy and Ethical Regime in Adekunle Ajasin University, Akungba Akoko, Ondo State, Nigeria - Dare Ezekiel Arowolo (University of Management and Technology, 2020)
Public service is regarded as the working hand of government, but it has recorded downward trends in its onerous responsibility of delivering services to the people in recent times. The performance crisis of public service perhaps explains the proliferation of literature on how to address the seeming impasse in the sector. However, there has to date been little systematic evaluation of the prevalence of X or Y theory as a motivational strategy, whereas X is assumed to enforce ethics while Y calls for participation. This study assessed the effect of the application of motivational strategies suggested by theory X and Y and its outcomes on employees' performance at Adekunle Ajasin University (AAUA) by using mixed-method techniques. The study found critical evidence that there was a concomitant relationship between ethics, motivation, and employees' performance and that the AAUA applied more of X than Y strategies for the motivation of its employees. Consequently, strained relationships have been witnessed between the unions and the university management, thereby impelling employees' performance. Therefore, it is recommended that the university must apply more participative Y type techniques than X type ethical codification as a strategy towards enhancing employee performance. The findings are relevant for understanding the dynamic role of ethics and motivation in the performance analysis of any public organization and for providing the necessary strategies for performance enhancement of public organizations.